Mid-infrared ultrafast carrier dynamics in thin film black phosphorus. (9th June 2017) - Iyer, Vasudevan; Ye, Peide; Xu, Xianfan
Abstract: Black phosphorus is emerging as a promising semiconductor for electronic and optoelectronic applications. To study fundamental carrier properties, we performed ultrafast femtosecond pump-probe spectroscopy on thin film black phosphorus mechanically exfoliated on a glass substrate. Carriers (electrons and holes) were excited to high energy levels and the process of carrier relaxation through phonon emission and recombination was probed. We used a wide range of probing wavelengths up to and across the band gap to study the evolution of the relaxation dynamics at different energy levels. Our experiments revealed a plethora of important physical phenomena. The fast relaxation time constants, associated with carrier-phonon scattering, steadily increase as the energy of the probe beam approaches the band gap energy, which was determined to be 0.31 eV, and the carrier recombination rate was obtained when the probe wavelength was tuned to match the band gap energy. The carrier-phonon scattering rates were found to be similar along the armchair and zigzag directions, therefore, the anisotropic carrier mobility reported in literature is mainly due to the difference in effective mass of carriers along different directions. The ultrafast spectroscopy data further revealed the oxidation induced surface charges. Our results highlight the importance of using the spectroscopy technique, in this case, in the mid-IR range, to uncover useful physical processes.